L’ethnographie militaire aux origines de la « politique berbère » du protectorat français au Maroc (1912-1915) - Mathieu Marly (L’Année du Maghreb)
This article focuses on the military archives produced in the Moroccan Middle Atlas between 1912 and 1915, in which the ethnonym “Berber” becomes an operative category of colonial power. For lack of extensive ethnographic surveys in this region of Morocco, officers were the first to collect and analyze available information on Berber-speaking populations with the tools, interpretative patterns, and prejudices of a military ethnography inspired by bureaux arabes and Sudanese circles. These archives of military ethnography were spaces of experimentation and uncertainty, in which officers analyzed information collected on “indigenous” populations, developed often contradictory hypotheses, and selected and forgot data, before their observations were fixed by the “Berber policy” of the French Protectorate in Morocco.This article first focuses on the prejudices that officers had toward the political legitimacy of the Maghzen, the “religious lukewarmness” of Berber populations, and the political role of the tribal framework in Morocco. It then shows that the Berber ethnonym was produced in an operational context linked to the “pacification” of the Middle Atlas. From 1913 onwards, a group of officers drew up a new political action plan based on the supposed unity of “Berber customs,” hoping to thereby rally the populations and facilitate the region’s “pacification.” This new approach is reflected in the military archives through the appearance of ethnographic questionnaires on Berber customs that complemented the “fiches de tribus.” It was only beginning in 1915 that members of the military called on representatives from the academic world to help shape their own conceptions of “Berber customs,” as inspired by their experiences with the Kabyle and Tuareg populations.